Using cutting planes in an interactive reference point approach for multiobjective integer linear programming problems - Alves, Maria João (1999)
We propose an interactive approach for multiple objective integer linear programming (MOILP) problems that combines the use of the Tchebycheff metric with cutting plane techniques. At each interaction, the method computes the nondominated solution for the MOILP problem that is closest to a reference point according to the Tchebycheff metric. The information provided by the decision maker in each dialogue phase is used to adjust the next reference point through a sensitivity analysis stage. Cutting plane techniques enable the method to take advantage of computations performed at previous iterations to solve the next scalarizing integer program. We address both theoretical issues and the computational implementation.